2001
DOI: 10.1105/tpc.010083
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Elimination and Cytosine Methylation Are Rapid and Reproducible Responses of the Genome to Wide Hybridization and Allopolyploidy in Wheat

Abstract: Interspecific or intergeneric hybridization, followed by chromosome doubling, can lead to the formation of new allopolyploid species. Recent studies indicate that allopolyploid formation is associated with genetic and epigenetic changes, although little is known about the type of changes that occur, how rapidly they occur, and the type of sequences involved. To address these matters, we have surveyed F1 hybrids between diploid species from the wheat (Aegilops and Triticum) group and their derived allotetraploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
278
3
10

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 436 publications
(305 citation statements)
references
References 23 publications
14
278
3
10
Order By: Relevance
“…However, the loss of the hybridization fragment(s) found here and in other works Liu et al, 1998a;Shaked et al, 2001) was observed in all enzymes that produced diagnosable polymorphism. Moreover, we checked hybrids and allopolyploids with methylation-sensitive and -insensitive isoschizomeric restriction enzymes and found the same RFLP profiles (data not shown).…”
Section: Mechanism Of Allopolyploidy-induced Sequence Eliminationsupporting
confidence: 65%
See 3 more Smart Citations
“…However, the loss of the hybridization fragment(s) found here and in other works Liu et al, 1998a;Shaked et al, 2001) was observed in all enzymes that produced diagnosable polymorphism. Moreover, we checked hybrids and allopolyploids with methylation-sensitive and -insensitive isoschizomeric restriction enzymes and found the same RFLP profiles (data not shown).…”
Section: Mechanism Of Allopolyploidy-induced Sequence Eliminationsupporting
confidence: 65%
“…Altered patterns of DNA methylation have been shown to be a frequent outcome in new allopolyploids (Song et al, 1995;Liu et al, 1998b;Shaked et al, 2001). However, the loss of the hybridization fragment(s) found here and in other works Liu et al, 1998a;Shaked et al, 2001) was observed in all enzymes that produced diagnosable polymorphism.…”
Section: Mechanism Of Allopolyploidy-induced Sequence Eliminationsupporting
confidence: 41%
See 2 more Smart Citations
“…It has been established that hybridization between genetically differentiated species or ecotypes may induce structural genomic changes (e.g., rearrangement) in the hybrids [1-7]. To address the genetic consequences of inter-specific hybridization, a larger number of studies have investigated the genetic variation patterns and molecular modes of the resultant hybrids.…”
Section: Introductionmentioning
confidence: 99%